Penerapan Konsep Interaksi Tata Guna Lahan-Sistem Transportasi Dalam Perencanaan Sistem Jaringan Transportasi - Ofyar Z. Tamin; Russ Bona Frazila (The Institute for Research and Community Services, Institut Teknologi Bandung, 1997)
Strong interaction between landuse and transportation system has been well and widely known by many transport planners. However, this concept is rarely being used in many transportation network planning projects. The parameter usually used is the trend of traffic growth. This kind of information is not very precise to be used for the transportation network development policy. This kind of information will give misleading results for the transportation network development policy.Basically, this interaction concept combines the regional development policy represented in the Regional Landuse Plan (national, province, kabupaten or city) with the Transport Network System which will accomodate the flows resulting from the activities carried out by each landuse. In fact, the landuse has a very strong causal relationship with the transport network system (road, rail, etc.)A quantitive model has been developed to relate the interaction between the Regional Landuse Plan and the Transport Network System (especially road) so that the transport network development policy, in fact, has anticipated and accomodated the changes due to the landuse development. This quantitive model can be used for different levels of planning such as: for landuse (national, regional island, province, kabupaten, city and ecen small local area) and for road transport network (arterial, collector, local, either primary or secondary). This paper will describe in detail the interaction concept in the form of a quantitive model and show the results of the application for planning the development of road transport network in East Java province.